Effect of liver dysfunction on outcome of radioactive iodine therapy for Graves’ disease - Yuyang Ze; Fei Shao; Xuefeng Feng; Shanmei Shen; Yan Bi; Dalong Zhu; Xiaowen Zhang (BMC Endocrine Disorders, 2022)
Abstract Liver dysfunction is a common complication of Graves’ disease (GD) that may be caused by excessive thyroid hormone (TH) or anti-thyroid drugs (ATDs). Radioactive iodine (RAI) therapy is one of the first-line treatments for GD, but it is unclear whether it is safe and effective in patients with liver dysfunction. 510 consecutive patients with GD receiving first RAI were enrolled in the study, and followed up at 3-, 6- and 12-month. Liver dysfunction was recorded in 222 (43.5%) patients. GD patients with liver dysfunction had higher serum levels of free triiodothyronine (FT3) (median 27.6 vs. 20.6 pmol/L, p < 0.001) and free thyroxine (FT4) (median 65.4 vs. 53.5 pmol/L, p < 0.001) levels than those with normal liver function. Binary logistic regression analysis showed that duration of disease (OR = 0.951, 95% CI: 0.992–0.980, p = 0.001) and male gender (OR = 1.106, 95% CI: 1.116–2.384; p = 0.011) were significant differential factors for liver dysfunction. Serum TSH levels were higher in patients with liver dysfunction at all 3 follow-up time points (p = 0.014, 0.008, and 0.025 respectively). FT3 level was lower in patients with liver dysfunction at 3-month follow-up (p = 0.047), but the difference disappeared at 6 and 12 months (p = 0.351 and 0.264 respectively). The rate of euthyroidism or hypothyroidism was higher in patients with liver dysfunction than in those with normal liver function at 3 months (74.5% vs 62.5%; p = 0.005) and 6 months (82.1% vs 69.1%; p = 0.002) after RAI treatment, but the difference did not persist at 12-month follow-up (89.6% vs 83.2%, p = 0.081).There were no statistically significant differences in treatment efficacy (94.48% vs 90.31%, p = 0.142), incidence of early-onset hypothyroidism (87.73% vs 83.67%, p = 0.277), and recurrence rate (4.91% vs 7.14%, p = 0.379) between the 2 groups at 12-month follow-up. In conclusion, the efficacy of RAI was comparable in GD patients with liver dysfunction and those with normal liver function.